Sobre o significado dos guerreiros lusitano-galaicos: o contributo da epigrafia (Palaeohispanica. Revista sobre lenguas y culturas de la Hispania Antigua, 2019)
Taking into account the Latin inscriptions presented in some statues of Callaico-Lusitanian warriors, which were subject of epigraphic revaluation, one discusses the meaning and significance they give to these sculptural manifestations.